The Role of Cytokines in Degenerative Retinal Diseases: A Comprehensive Review - Rubens Camargo Siqueira; Cinara Cássia Brandão (Biomedicines)
Degenerative retinal diseases, such as age-related macular degeneration (AMD), diabetic retinopathy (DR), and retinitis pigmentosa (RP), are the leading causes of vision loss worldwide. Inflammation plays a crucial role in the pathogenesis of these diseases, with cytokines acting as key mediators of neuroinflammation, vascular dysfunction, and cellular degeneration. This review explores the complex role of cytokines in degenerative retinal diseases, highlighting their involvement in disease progression, cellular interactions, and potential therapeutic strategies. Understanding the cytokine network within the retina may provide novel insights into targeted interventions for these debilitating conditions.